Analisis Kepatuhan Pelaku Usaha Terhadap Undang-Undang Perlindungan Konsumen di Indonesia - Islami MQ. Baba, Amiruddin (Media Hukum Indonesia (MHI), 2025)
This study aims to analyze consumer protection in e-commerce transactions in Indonesia by examining the legal framework, implementation, business compliance, and consumer awareness. Using a descriptive normative approach, the research reviews key regulations such as Law Number 8 of 1999 on Consumer Protection, the Personal Data Protection Law of 2022, and Government Regulation Number 80 of 2019 on Trading Through Electronic Systems. The analysis reveals that although the existing regulations provide a strong legal foundation, their implementation still faces several challenges, including low consumer legal literacy, weak law enforcement, and limited understanding among business actors, particularly MSMEs. Therefore, enhancing consumer protection in the e-commerce sector requires collaboration between the government, business entities, and society, focusing on digital education, transparency, and the strengthening of monitoring and online dispute resolution mechanisms.